Forecasting Load on PT PLN (Persero) Metro Substations (GI) Using Combined Methods for Electrical Needs in Metro City 2019 - 2029 - Candra Saigustia (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2019)
Abstract Electricity consumption in Metro City has increased along with the increase in population, economic activity, technological progress and growth of households. Electrical energy is needed for the interests of industry, households and other activities as well as to support increasingly advanced technological developments The researcher used load forecasting with a combined method based on economic growth, population growth, and the growth of households in Metro City. The data used in this study are growth data that occurred from 2014 to 2018. The results of this paper is forecasting the number of customers, load energy consumption (MWh), total energy requirements (MWh), connected power (kVA), and peak load (MW). Energy consumption growth every year has the same tendency as in previous years. In the household sector, energy consumption will grow higher each year than other sectors. In 2029, it estimated that the peak load that will occur at Metro substations, PT PLN (Persero) Rayon Metro City is 92.62 MW. Keywords — Forecasting, Electrical Energy Needs, Combined Method, PT PLN, Metro City